Visible radiophotoluminescence of colour centres in lithium fluoride: from lasers to versatile radiation sensors. Issue 1 (1st August 2022) - Montereali, R.M.; Bonfigli, F.; Nichelatti, E.; Nigro, V.; Piccinini, M.; Vincenti, M.A.
Abstract: The peculiar photoluminescence characteristics of radiation-induced colour centres in lithium fluoride (LiF), well known for applications in optically-pumped tuneable lasers and broad-band miniaturised light-emitting photonic devices operating at room-temperature, are under exploitation in passive imaging detectors and dosimeters based on visible radiophotoluminescence in LiF crystals and polycrystalline thin films. Their high intrinsic spatial resolution, wide dynamic range and large field of view, combined with easy handling, ambient-light operation and no development need, allow to successfully extend their use from X-ray imaging to proton-beam advanced diagnostics and dosimetry, even at those low dose values that are typical of hadrontherapy. After exposure, the latent images stored in LiF as local formations of F2 and F3 + aggregate defects are read with an optical fluorescence microscope under illumination in the blue spectral range. Their visible emission intensity was found to be linearly proportional to the dose over at least three orders of magnitude, so that bi-dimensional LiF solid-state dosimeters based on spectrally-integrated radiophotoluminescence reading can be envisaged. Taking advantage of the low thickness of LiF thin films, transversal proton beam dose mapping was demonstrated at low proton energies, even at high doses. Recent results and advances concerning LiF crystals and polycrystalline thin film characterisation in the linearity range are presented and discussed with the aim of highlighting challenges related to increasing the LiF film detector radiation sensitivity to both particles (protons) and photons (X-rays), although therapeutic dose values typical of clinical radiotherapy are still a big challenge.